Environmental liabilities, borrowing costs, and pollution prevention activities: The nationwide impact of the Apex Oil ruling - Chen, Jianqiang; Hsieh, Pei-Fang; Hsu, Po-Hsuan; Levine, Ross (Journal of Corporate Finance, 2025)
The 2008 Apex Oil court decision reduced the circumstances under which specific environmental cleanup obligations were dischargeable in Chapter 11, potentially affecting the securities prices, credit conditions, and pollution practices of corporations not in Chapter 11. We discover that among financially stressed firms with those specific environmental liabilities, bond and stock prices dropped after Apex. Moreover, those firms (1) experienced a tightening of credit conditions (e.g., paying higher risk premia on debts and receiving lower bond ratings), (2) intensified pollution prevention activities, and (3) reduced the emissions of pollutants causing environmental damages no longer dischargeable in Chapter 11. These findings hold among firms nationwide, not only those within the jurisdiction of the Seventh Circuit court, which issued the Apex decision, suggesting that Apex had a nationwide impact.